Reconstruction of Kiai Management Based on Charismatic Leadership as a Model for Strengthening the Soft Skills of Abdi Ndalem Students in Islamic Boarding Schools - Lilis Sholihatul Jannah; M.Fahim Tharaba (Journal of Educational Management Research, 2026)
This research is motivated by the importance of strengthening soft skills in education, which has not been fully accommodated in the formal education system. Islamic boarding schools (pesantren) as value-based institutions have the potential to develop soft skills through the practice of student service. This study aims to reconstruct kiai management based on charismatic leadership as a model for strengthening the soft skills of student servants. The study used a qualitative approach with a case study design at the Al-Yasini Integrated Islamic Boarding School, through interviews, observations, and documentation. The results show that kiai management occurs culturally through values, role models, and interpersonal relationships, and that soft skills strengthening occurs through experiential learning in the practice of service. This study produces a conceptual model that integrates charismatic leadership, the service process, and soft skills strengthening. The contribution of this research lies in the development of a value-based Islamic education management model. It is concluded that kiai management is effective in shaping the character and social readiness of students in a sustainable manner.